(untitled) (Revista Electrónica REDINE, 2018)
The intent of the research is the construction of a theoretical approach to the communicative dimension of language as action in the managerial performance. It is done from the phenomenological and hermeneutical approach proposed by Habermas (2000), for the study of action seeking the understanding of facts. Methodologically this research uses the depth interview for collecting information. It is institutionally developed in the core Hector Ochoa Zuleta. Agronomy deanship. Lisandro Alvarado University. Located in Cabudare, Lara state. Key informants were: managers, responsible for activities such as crop production, teaching, extension and research. The data was collected and subjected to micro - analysis and other specific considerations and constant comparative method in version Strauss and Corbin (2002), used to generate Grounded Theory. Among the findings it is seen that the manager, subject capable of speech and action is oriented to the search for understanding, from the way of acting himself that involves a style marked by recognizing the other as legitimate, loyalty to the institution and values such as democracy and ethics. All it revealed in emerging categories: Performance, organizational environment and management style. As integrator elements to build substantive theory emerged as main category: minds for action, due to it are the axis where gravitates the possibility of manager cohesion action. Without this the teleological character of the organization is committed. Among final thoughts highlights that understanding for the action allows the organizational phenomenon, but as this occurs depends on the style of management